Structural, plasmonic and electronic properties of zirconium carbonitride thin films prepared by dual ion beam deposition - Liu, Tingting; Ran, Yujing; Wang, Tianrun; Yu, Xiaoting; Hu, Guangxiao; Jiang, Zhaotan; Wang, Zhi (Applied physics. A, Materials science & processing, 2023)
Metal carbonitride is a new type of tunable plasmonic materials and can be tuned by nitrogen and carbon content. In this work, zirconium carbonitride (ZrC x N y ) thin films are prepared by dual ion beam deposition. The effects of C content and assisting ions on the structure and plasmonic properties of the films are studied. The results show that all the films are in B1-structure. C content increasing can reduce the shielding plasma frequency ħ ω c and the carrier concentration of the film. Appropriate assisting ion beam energy E a and current density J a can promote the crystallinity of the film. As E a and J a increases, ħ ω c increases initially and then decreases. The effects of the assisting ions can be attributed to the C content and the C-related defects, which is confirmed by the calculation of electronic states. The calculated density of state of the electrons shows that increasing C-substitute defects can decrease the threshold energy of interband transition, and the interstitial C defects lead to the similar effect. The study shows that metal carbonitride is a more tunable plasmonic material in visible and infrared region, and can also be modulated by the assisting ions.